Issues on monitoring and simulating the thermo-mechanical behaviour of concrete since early ages - Azenha, Miguel (2012)
Even though the numerical simulation of concrete at early ages is an issue that has been studied for decades with thermo-mechanical approaches, several doubts still exist in the scientific community in regard to the modeling strategies and accuracy of predictions. In view of such challenges, the teams of the University of Minho and the University of Porto have been conducting research in the field, following a holistic strategy that encompasses: (i) material characterization in laboratory, (ii) thermo-mechanical simulation and (iii) in-situ monitoring for validation of simulations. The present paper aims to provide information about our current state of knowledge in these three vectors, while discussing limitations and development prospects.